2011
DOI: 10.1016/j.jpsychores.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Two sessions of sleep-focused mind–body bridging improve self-reported symptoms of sleep and PTSD in veterans: A pilot randomized controlled trial

Abstract: This study provides preliminary evidence that a brief sleep-focused MBB could be a promising intervention for sleep and potentially other comorbid symptoms (e.g., PTSD). MBB could help patients develop awareness skills to deal with sleep-related symptoms. Integration of MBB into primary care settings may enhance care of patients with sleep disturbance and co-morbid symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 42 publications
3
71
0
Order By: Relevance
“…A variety of outcome measures assessing PTSD symptoms in either self-report or clinician-administered formats were employed: PTSD checklist/PTSD checklist -military (PCL/PCL-M) (Germain et al, 2012;Nakamura, Lipschitz, Landward, Kuhn, & West, 2011;Rose, 2013;Talbot et al, 2014;Ulmer, Edinger, & Calhoun, 2011;Ustinov, 2013), PTSD symptom scale/modified PTSD symptom scale (PSS/ MPSS) (Davis & Wright, 2007;Krakow et al, 2000Krakow et al, , 2001aMack, 2013;Margolies, Rybarczyk, Vrana, Leszczyszyn, & Lynch, 2013), trauma symptom inventory (TSI) (Davis et al, 2011), and Clinicianadministered PTSD scale (CAPS) (Davis et al, 2011;Krakow et al, 2000Krakow et al, , 2001aTalbot et al, 2014). Self-report and clinicianadministered measures of MDD symptoms included Beck depression inventory (BDI) (Davis & Wright, 2007;Germain et al, 2012;Talbot et al, 2014;Ustinov, 2013), patient health questionnaire (PHQ) (Mack, 2013;Margolies et al, 2013;Ulmer et al, 2011), center for epidemiological studies -depression (CES-D) (Nakamura et al, 2011), and trauma symptom inventory (TSI) (Davis et al, 2011). Self-report sleep measures included Pittsburgh sleep quality index (PSQI) (Davis & Wright, 2007;Davis et al, 2011;Germain et al, 2012;Krakow et al, 2000Krakow et al, , 2001aMack, 2013;Margolies et al, 2013;Rose, 2013;Talbot et al, 2014;Ulmer et al, 2011), sleep diary …”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…A variety of outcome measures assessing PTSD symptoms in either self-report or clinician-administered formats were employed: PTSD checklist/PTSD checklist -military (PCL/PCL-M) (Germain et al, 2012;Nakamura, Lipschitz, Landward, Kuhn, & West, 2011;Rose, 2013;Talbot et al, 2014;Ulmer, Edinger, & Calhoun, 2011;Ustinov, 2013), PTSD symptom scale/modified PTSD symptom scale (PSS/ MPSS) (Davis & Wright, 2007;Krakow et al, 2000Krakow et al, , 2001aMack, 2013;Margolies, Rybarczyk, Vrana, Leszczyszyn, & Lynch, 2013), trauma symptom inventory (TSI) (Davis et al, 2011), and Clinicianadministered PTSD scale (CAPS) (Davis et al, 2011;Krakow et al, 2000Krakow et al, , 2001aTalbot et al, 2014). Self-report and clinicianadministered measures of MDD symptoms included Beck depression inventory (BDI) (Davis & Wright, 2007;Germain et al, 2012;Talbot et al, 2014;Ustinov, 2013), patient health questionnaire (PHQ) (Mack, 2013;Margolies et al, 2013;Ulmer et al, 2011), center for epidemiological studies -depression (CES-D) (Nakamura et al, 2011), and trauma symptom inventory (TSI) (Davis et al, 2011). Self-report sleep measures included Pittsburgh sleep quality index (PSQI) (Davis & Wright, 2007;Davis et al, 2011;Germain et al, 2012;Krakow et al, 2000Krakow et al, , 2001aMack, 2013;Margolies et al, 2013;Rose, 2013;Talbot et al, 2014;Ulmer et al, 2011), sleep diary …”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…50 These well-established scales have been shown to be sensitive to short-term behavioral interventions, and have been validated in a wide range of populations, including patients with RLS. [51][52][53][54][55][56][57][58][59][60] Blood pressure and heart rate were measured with subjects in a seated position following a 5-minute rest period; using the OMRON HEM-780 automatic blood pressure monitor, measurements were taken 3 times and averaged for a final score.…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…This dysfunctional process perpetuates maladaptive thoughts, feelings and behaviors and, in MBB, is heuristically "personified" as an "Identity System" that can be activated when an individual encounters triggering situations or undesirable outcomes. MBB has been investigated as a short-term intervention for managing disturbed sleep and other co-occurring symptoms [17], as well as for dealing with various issues associated with substance misuse/abuse conditions, using MBB as a complementary intervention added to standard care [18]. Clinical trials have demonstrated that MBB, compared to a mindfulness meditation condition, can be relatively more fast-acting and equally long-lasting in promoting mind-body wellbeing, after only three weekly sessions [19].…”
Section: Introduction Of Mind-body Bridgingmentioning
confidence: 99%